Properties of a new insulation material glass bubble in geopolymer concrete - Shahedan, Noor Fifinatasha; Abdullah, Mohd Mustafa Al Bakri; Mahmed, Norsuria; Kusbiantoro, Andri; Tammas-Williams, Sam; Long, Yuan Li; Aziz, Ikmal Hakem; Vizureanu, Petrica; J. Wysłocki, Jerzy; Błoch, Katarzyna; Nabiałek, Marcin (MDPI, 2021)
This paper details analytical research results into a novel geopolymer concrete embedded with glass bubble as its thermal insulating material, fly ash as its precursor material, and a combination of sodium hydroxide (NaOH) and sodium silicate (Na2SiO3) as its alkaline activator to form a geopolymer system. The workability, density, compressive strength (per curing days), and water absorption of the sample loaded at 10% glass bubble (loading level determined to satisfy the minimum strength requirement of a load-bearing structure) were 70 mm, 2165 kg/m3, 52.58 MPa (28 days), 54.92 MPa (60 days), and 65.25 MPa (90 days), and 3.73 %, respectively. The thermal conductivity for geopolymer concrete decreased from 1.47 to 1.19 W/mK, while the thermal diffusivity decreased from 1.88 to 1.02 mm2/s due to increased specific heat from 0.96 to 1.73 MJ/m3K. The improved physicomechanical and thermal (insulating) properties resulting from embedding a glass bubble as an insulating material into geopolymer concrete resulted in a viable composite for use in the construction industry.